AKTUALISASI DIRI TOKOH AKIKO DALAM NOVEL YURICHIKA E MAMA KARA NO DENGON KARYA AKIKO TERENIN - Mrs, Fitriana (Humanis; Volume 13. No.2. Nopember 2015)
This thesis entitled Self actualization of Akiko’s figure in the novel Yurichika E Mama Kara no Dengon by Akiko Terenin. The purposes of this study are to know forms of self actualization of Akiko after suffer malignant tumors and to know moral message conveyed through Akiko Terenin’s view against self actualization of Akiko’s figure in the novel Yurichika E Mama Kara no Dengon by Akiko Terenin. This research used descriptive analysis and formal methods as methods and techniques of data analysis. The theories used in this study are a multilevel needs theory by Maslow and genetic structuralism theory by Goldmann. Based on the analysis, this research result  explains about Akiko who want to actualize herself to become a useful person for her daughter and others until she died later, also found 10 characteristics of self actualization in Akiko’s figure  in the novel Yurichika E Mama Kara no Dengon by Akiko Terenin, namely: (1) observed the reality efficiently; (2) Acceptance of self, others, and fate; (3) Focused on problem; (4) Independence of culture and environment; (5) Freshness and appreciation; (6) Social interest; (7) Interpersonal relationships; (8) Democratic character; (9) The difference between means and ends; (10) creativity. Furthermore,  there are three moral messages conveyed by Akiko Terenin through the novel, namely (1) receiving with sincerity; (2) not easily discouraged; (3) independent and responsible.
Keywords: Self actualization, Moral message, Psychology of literature